Entre la literatura i la divulgació científica: les novel·les de Martí Domínguez - Łuczak, Barbara (Studia Romanica Posnaniensia, 2015)
Martí Domínguez (1966) is a biologist, writer and journalist, the author of novels, essays, and press articles. In his novels Les confidències del comte de Buffon (1997) and El secret de Goethe (1999), he presents two great personalities of 18th century Europe and a scientific and cultural context of their lives and works. These novels contain information about debates, ideas, and theories related to the development of science (especially the natural sciences) in the Age of Enlightenment. In the article we study the narrative strategies used by the author in order to present issues regarding the history of natural sciences in modern Europe.